2008
DOI: 10.4312/dp.35.6
|View full text |Cite
|
Sign up to set email alerts
|

Warfare in Late Neolithic\Early Chalcolithic Pisidia, southwestern Turkey. Climate induced social unrest in the late 7th millennium calBC

Abstract: This paper proposes an association between climate forcing connected with the 8200 calBP ‘climate event’ and a postulated phase of internecine warfare and population collapse at Late Neolithic/Early Chalcolithic sites in Pisidia, southwestern Turkey. A summary of this evidence is provided and a hypothetical scenario considered in the context of contemporaneous developments in neighbouring regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…The onset of Neolithisation in northwest Anatolia is associated with factors such as innovation of agricultural practices to be suitable for more temperate climates and social transformations inducing migration from central Anatolia. In addition, there is a period of climatic instability between 8.6 and 8.0 ka cal BP which recent studies indicate as marked by increased winter extremes in addition to periods of drought and extreme rainfall (Clare et al, 2008; in press), affecting primarily local communities in central and in northwest Anatolia (Düring, 2013;Weninger et al, 2014). The influence of this period of cold conditions with a general arid trend is reflected in this study, as a retreating lake margin has been found prior to the oldest habitation at the site.…”
Section: Settlement Locationmentioning
confidence: 95%
“…The onset of Neolithisation in northwest Anatolia is associated with factors such as innovation of agricultural practices to be suitable for more temperate climates and social transformations inducing migration from central Anatolia. In addition, there is a period of climatic instability between 8.6 and 8.0 ka cal BP which recent studies indicate as marked by increased winter extremes in addition to periods of drought and extreme rainfall (Clare et al, 2008; in press), affecting primarily local communities in central and in northwest Anatolia (Düring, 2013;Weninger et al, 2014). The influence of this period of cold conditions with a general arid trend is reflected in this study, as a retreating lake margin has been found prior to the oldest habitation at the site.…”
Section: Settlement Locationmentioning
confidence: 95%
“…Due to the lack of datable material, the deposition of Unit C is difficult to specify further than within the Early Holocene. However, it can be claimed that Unit E is only slightly older than the earliest occupation phases since there are no other deposits or apparent hiatuses separating the anthropogenic units from Unit E. This dates the interpreted lake shore deposits just slightly before~8550 a cal BP in the Early Holocene, which coincides with the onset of a period of climatic instability around 8600 a cal BP, that is thought to be characterised by generally colder winters with pronounced extremes of dry and wet conditions (Clare et al, 2008;Weninger et al, 2009;Clare and Weninger, in press). The dating of these deposits as well as the start of occupation of the site early in, or perhaps even slightly before, this period disproves a link between environmental change and the northwest Anatolian spread of farming with rapid climate change known as the 8.2 ka cal BP event (Weninger et al, 2006).…”
Section: Environmental Evolutionmentioning
confidence: 95%
“…One notable cold event is known as the 8.2 ka cal BP event (Barber et al, 1999), which is also cited in some studies in relation to Neolithisation in the eastern Mediterranean (Weninger et al, 2006). However, this short event falls into a longer period of climate change between 8.6 and 8.0 ka cal BP (Rohling and P€ alike, 2005), where cold winters with more extreme periods of drought and excessive rainfall generally became more dominant (Clare et al, 2008;Clare and Weninger, in press). …”
Section: Landscape and Climatementioning
confidence: 96%
See 1 more Smart Citation
“…Clare et al (2008) suggest that a well-documented major cold-arid episode around 8200 calendar years before present (hereafter abbreviated to BP) was linked with internecine warfare and population collapse at sites in southwestern Turkey. More well known is a qualitatively similar episode around 4200 BP, which has been linked with the collapse of the Akkadian Empire (Cullen et al, 2000;deMenocal, 2001), the end of the Egyptian Old Kingdom (Stanley et al, 2003), and the collapse of Neolithic cultures in north-central China (Chen et al, 2005;Wenxiang & Tungsheng, 2004).…”
Section: Introductionmentioning
confidence: 98%